Pengaruh Social Media Influencer Terhadap Perilaku Konsumtif di Era Ekonomi Digital - Irfan Maulana; Jovanna Merseyside br. Manulang; Ossya Salsabila (Majalah Ilmiah Bijak, 2020)
This study aims to determine the correlation between consumptive behavior at using e-commerce in this digital era and social media influencers. The background of this study is the rapid growth of e-commerce in Indonesia. Quantitative descriptive method was being used to found the causal relationship among dependent and independent variable for the e-commerce users in this digital era. The data collection technique was carried out with the study of literature by collecting information from various sources relevant to the research object. The results showed that in 2018 there were 72.83% of businesses selling via the internet with an online shopper which increased from year to year, where the number reached 11.9% of the total population in Indonesia. The results of other studies indicate that the level of public trust in social media in 2018 is 51%, based on public behavior from information written by journalists, global report platforms, and social media influencers. The information is in the form of news, educational activities, communication, and trading activities. From these results, there is a correlation between the high of consumptive behavior in the use of e-commerce and social media influencers who are influenced by the credibility of the influencers, thereby increasing consumptive behavior in the digital era.